PENGGUNAAN ALAT PERMAINAN EDUKATIF UNTUK MENINGKATKAN KREATIVITAS ANAK DI TK - Muyasaroh (AS-SALAM, 2013)
In the process of educating at TK (Primary School), one of the main goalsis to develop the creativity of children optimally. It is so important aboutdeveloping the creativity of children can be seen from the difference ofthe role of the teacher which is early dominating a class, now must givemore a chance to the children to take a more active and creative role in thecomfortable atmosphere and that is supported with supplying educativegames. That dimension is underlying this research.This research heads for increasing the creativity of children through usingthe tools of educative games. Those tools which are used are origami paper,poster paint, and plastisin. The kind of this research is a research of classaction, because this research is relevant and agrees with the object ofresearch. The subject of this research is all of the pupils in group BI in TKABA I Braja Harjosari, 32 Pupils.The collecting of data that is collected in this research is observation,interview/discussion, and documentation. This research is going to actin cycle I and II around six times meeting. After analyzing and workingthrough in this research, the writer can take the conclusion that the usingtools of educative games can increase the creativity of the children age 5-6years. It can be proved with the percentage of !inal learning to cycle I up to56, 25% and then increasing at the cycle II becomes 71, 87%